(untitled) (Global Journal of Human-Social Science, 2014)
A slum is a compact area of overcrowded population, poorly built congested dwelling condition, unhygienic environment usually with inadequate infrastructure and lacking in proper sanitary and drinking water facilities. Living conditions in slums have a direct impact on people’s health. One of the major challenges that face urban planners globally is the proliferation of slums in urban areas and the host of health hazards that they bring along with their wake. However, the prolific spread of slums has been a rampant problem in urban areas worldwide. Eventually, the extent and spread of slums in India not only help us to recognize that they are not anomalous and pathological phenomena on the urban landscape but also a manifestation of urban poverty that is still predominant in the urban economy. This study is an attempt to unfold the underlying problems of development of slums.